Gastric Outlet Obstruction: A Case Report - Deepali Ghungrud1 , Vaishali Tembhare2 , Sheetal Sakharkar3, Manoj Patil4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Gastric outlet obstruction is an obstruction in the pylorus of stomach it is also known as apyloric obstruction. It is a common condition but sometimes accurate cause could not be found in thesecases it can be diagnosed on the basis of signs and symptoms and on diagnostic evaluation i.e endoscopicexamination, barium meal, ultrasonogaphy, computed tomography and chest x-ray.Case Presentation: Here we are mentioninga 50- year’sold male visited our hospital with the complaintsof severe abdominal pain, nausea and vomiting since 2 days, weakness since 5 months, has passed stool 2days ago, weight loss for 2 months. All routine laboratory tests were done in this case and all the resultswere within normal range except decreased hemoglobin level, increase in white blood cells also increasedcreatinine level and decreased albumin level. In Abdominal ultrasonography it was mentioned that severelyedematous mucosa with erosive patches and places, Pyloric canal deformed scope could not be negotiatedacross the pylorus. Barium meal study depicted dilated stomach where greater curvature is below the levelof iliac crest. Finally a client case was diagnosed as a gastric outlet obstruction. Primarily as per priorityBlood transfusion and all conservative treatment was started by surgical team but client was not relievedof obstruction by the medical management. Diagnostic exploratory laparotomy with repair of duodenalperforation with gastrojejunostomy under general anesthesia was done. Vital signs and cardiac monitoringwas done. Maintained intravenous fluid and colour of drainage was observed, propped up position andantibiotic, analgesic, anti emetic given and ryle’s tube aspiration was done 4 hourly also abdominal girth wasalso measured 4 hourly. A positive response to treatment was observed by patient. Patient was dischargedwith full recovery without any postoperative complication.Conclusion: In this study, we mainly focus on expert surgical management and quality nursing care dueto which the patient was discharged without any postoperative complications and satisfaction with fullrecovery